HIV infection and arterial stiffness among older-adults taking antiretroviral therapy in rural Uganda. (20th February 2016) - Siedner, Mark J.; Kim, June-Ho; Nakku, Ruth Sentongo; Hemphill, Linda; Triant, Virginia A.; Haberer, Jessica E.; Martin, Jeffrey N.; Boum, Yap; Kwon, Douglas S.; Tsai, Alexander C.; Hunt, Peter W.; Okello, Samson; et al.
Abstract : HIV infection is associated with arterial stiffness, but no studies have assessed this relationship in sub-Saharan Africa. We enrolled 205 participants over 40 years old in Uganda: 105 on antiretroviral therapy for a median of 7 years, and a random sample of 100 age and sex-matched HIV-uninfected controls from the clinic catchment area. The prevalence of arterial stiffness (ankle brachial index  > 1.2) was 33%, 18%, 19% and 2% in HIV+ men, HIV– men, HIV+ women, and HIV– women. In multivariable models adjusted for cardiovascular risk factors, HIV+ individuals had over double the prevalence of arterial stiffness (adjusted prevalence ratio 2.86, 95% confidence interval 1.41–5.79, P  = 0.003). Abstract : Supplemental Digital Content is available in the text